2022
DOI: 10.2217/fon-2022-0378
|View full text |Cite
|
Sign up to set email alerts
|

Physician treatment preferences for relapsed/refractory multiple myeloma: a discrete choice experiment

Abstract: Aim: This study aimed to assess physician preferences for later lines (third to fifth) of therapy in patients with relapsed/refractory multiple myeloma (RRMM) in the USA. Materials & methods: Factors relevant to physicians' treatment preferences for RRMM were identified from a literature search and refined in a qualitative phase. Preferences were quantitatively assessed using a discrete choice experiment. Physicians (n = 227) made choices regarding treatment scenarios for RRMM. Results: Efficacy had the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…A previously published DCE that evaluated physician treatment preferences for patients with relapsed/refractory multiple myeloma reported that overall survival was the highest priority when making treatment decisions. 33 However, that DCE included clinical and safety outcomes such as overall survival, overall response rate, progression-free survival, thrombocytopenia, and neutropenia, which may not be equivocal to the preferences included for evaluation in the current study. Similarly, in a DCE evaluating patient frontline treatment preferences for acute lymphoblastic leukemia, overall survival was the highest priority.…”
Section: Discussionmentioning
confidence: 96%
“…A previously published DCE that evaluated physician treatment preferences for patients with relapsed/refractory multiple myeloma reported that overall survival was the highest priority when making treatment decisions. 33 However, that DCE included clinical and safety outcomes such as overall survival, overall response rate, progression-free survival, thrombocytopenia, and neutropenia, which may not be equivocal to the preferences included for evaluation in the current study. Similarly, in a DCE evaluating patient frontline treatment preferences for acute lymphoblastic leukemia, overall survival was the highest priority.…”
Section: Discussionmentioning
confidence: 96%
“…A key driver of discordance between patients and physicians could be differences in priorities for treatment outcomes. Previous studies show that increasing survival is the most important outcome of treatment for both patients and physicians [ 11 ], but patients also place high importance on other factors, such as avoiding treatment side effects [ 12 ]. In the present study, HRQoL appeared worse in patients who reported higher levels of side-effect bother, suggesting that perception of treatment side effects influenced HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…With each successive LOT, treatment options for patients with MM have become increasingly complex due to the number of available regimens for patients with relapsed/refractory MM (RRMM) [ 4 ]. Studies have shown that in real-world practice, physicians tend to have a greater focus on survival outcomes when making treatment choices, with less consideration of other factors such as side effects and the need for patient visits [ 11 ]. Although patients also prioritize survival, they place higher importance on additional factors known to influence HRQoL, such as minimizing treatment side effects and offsetting financial burdens [ 12 ].…”
Section: Introductionmentioning
confidence: 99%